Blood Stream Infection by Escherchia hermannii in a Neonate - SMITA SOOD; SATYEN K HEMRAJANI (Journal of Clinical and Diagnostic Research, 2016)
Escherichia hermannii is a Gram negative bacillus, facultative anaerobe and member of the family Enterobacteriaceae. It was earlier classified as Enteric Group 11 by the Enteric Section of Centers for Disease Control (CDC) and was reported in the clinical laboratory as a yellow pigmented E. coli strain. On the basis of its unique genomic features, this organism was labelled as a distinct species in 1982. A successfully treated case of a blood stream infection by E. hermannii in a neonate is being described.